FROM THE LANGUAGE OF THE GODS TO THE VOICE OF THE PEOPLE: SANSKRIT, KASHMIRI VERNACULARISATION, AND LITERARY IDENTITY - Sheeba Hassan (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
This paper explores the rich literary and cultural heritage of Kashmir, tracing its evolution from Sanskrit to Persian and Kashmiri traditions. Lal Ded, a 14th-century poet, profoundly influenced the Kashmiri language, spirituality, and artistic expression through her vatsun verses. The romantic saga of Yousuf Shah Chak and Habba Khatoon in 16th-century Kashmir exemplifies how poetry served as both a medium of personal expression and a form of political resistance, thereby preserving Kashmiri cultural identity. The region’s composite culture is further illuminated by its multilingual traditions, which encompass Sanskrit, Persian, and Kashmiri. The historical development of Kashmir’s religious, political, and cultural landscape is also examined, including the influence of Sufism, the role of shrines, and the contemporary challenges facing the Kashmiri language and culture.